Are All Labor Regulations Equal ? : Assessing The Effects of Job Security, Labor Dispute, And Contract Labor Laws In India - Pagés, Carmen 2000- (The World Bank, 2007)
This paper studies the economic effects of legal amendments on different types of labor laws. It examines the effects of amendments to labor dispute laws and amendments to job security legislation. It also identifies the effects of legal amendments related to the most contentious regulation of all-Chapter Vb of the Industrial Disputes Act-which stipulates that firms with 100 or more employees cannot retrench workers without government authorization. The analysis finds that laws that increase job security or increase the cost of labor disputes substantially reduce registered sector employment and output but do not increase the labor share. Labor-intensive industries, such as textiles, are the hardest hit by laws that increase job security while capital-intensive industries are most affected by higher labor dispute resolution costs. The paper concludes that widespread and increasing use of contract labor may have brought some output and employment gains but did not make up for the adverse effects of job security and dispute resolution laws